Centranthus pontecorvi (Valerianaceae) a new species from Sardinia - Bacchetta, Gianluigi; Cambria, Salvatore; de Castro, Olga; Fenu, Giuseppe; Brullo, Salvatore (Phytotaxa, 2024)
The species of Centranthus (Valerianaceae) belonging to C. sect. Nervosae are investigated. They are currently represented by C. trinervis from southern Corsica and C. amazonum from central-eastern Sardinia. In addition, a new isolated population has been discovered in southwestern Sardinia, which is morphologically and ecologically very differentiated from the other two known species. This population can be treated as new species, named C. pontecorvi, growing on screes constituted by Cambrian metacarbonates, localized in the Sulcitano-Iglesiente biogeographic sector. For each species, a detailed description and a new illustration based on living and herbarium materials are provided. Information on typification, synonymy, phenology, ecology, distribution, conservation status, and a list of examined herbarium specimens is also given. Furthermore, an updated identification key utilising the diagnostic traits of these three species has been elaborated.